Chryseobacterium aquifrigidense FANN1 Produced Detergent-Stable Metallokeratinase and Amino Acids Through the Abasement of Chicken Feathers - Bokveld, Amahle; Nnolim, Nonso E.; Nwodo, Uchechukwu U. (Frontiers in Bioengineering and Biotechnology, 2021)
Microbial keratinases’s versatility in the benefication of keratinous waste biomass into high value products prompts its application in diverse sphere hence, advancing green technology and the bioeconomy. Consequently, a feather-degrading Chryseobacterium aquifrigidense FANN1 was used to produce keratinase, and its biochemical properties determined. The fermentation process conditions were optimized, and the liberated amino acids in the cell-free hydrolysates profiled. FANN1 showed a maximum keratinase yield of 1664.55 ± 42.43 U/mL after 72 h, at optimal process conditions that included initial medium pH of 8, incubation temperature of 30oC, 4% inoculum size (v/v), and 15 (g/L) of chicken feathers. Analysis of degradation product showed 50.32% and 23.25% as the protein value and total free amino acids, respectively, with a relatively high abundance of arginine (2.25%) and serine (2.03%). FANN1 keratinase was optimally active at pH 8.0 and relatively moderate to high temperature (40–50oC). EDTA and 1,10-phenanthroline inhibited the keratinase activity, and that suggests a metallo-keratinase. FANN1 keratinase showed remarkable stability in the presence of chemical agents, with residual activity 141 ± 10.38%, 98 ± 0.43%, 111 ± 1.73%, 124 ± 0.87%, 104 ± 3.89%, 107 ± 7.79%, and 112 ± 0.86% against DTT, H2O2, DMSO, acetonitrile, triton X-100, tween-80, and SDS, respectively. The residual activity of FANN1 keratinase was enhanced by Sunlight (129%), Ariel (116%), MAQ (151%), and Surf (143%) compared to the control after 60 min preincubation. Likewise, the enzyme was remarkably stable in the presence Fe3+ (120 ± 5.06%), Ca2+ (100 ± 10.33%), Na+ (122 ± 2.95%), Al3+ (106 ± 10.33%); while Co2+ (68 ± 8.22%) and Fe2+ (51 ± 8.43%) elicited the most repressive effect on keratinase activity. The findings suggest that C. aquifrigidense FANN1 is a potential candidate for keratinous wastes bio-recycling, and the associated keratinase has a good prospect for application in detergent formulation.